Retrospective study of aldosterone and progesterone secreting adrenal tumors in 10 cats. (2nd September 2021) - Harro, Cailin C.; Refsal, Kent R.; Shaw, Nicole; Alston, Samantha M.; Folger, William; Gross, Carolyn; Cousins, W. Mark; Monahan, Colleen F.; Mazaki‐Tovi, Michal; Langlois, Daniel K.
Abstract: Background: Primary hyperaldosteronism caused by adrenal neoplasia has been well described in cats. Multiple corticosteroid abnormalities occur in a subset of affected cats, but characterizations of this syndrome are limited to several case reports. Objectives: To describe a series of cats with adrenal tumors secreting aldosterone and additional corticosteroids. Animals: Ten cats with multiple corticosteroid secreting adrenocortical tumors. Methods: Retrospective case series. Medical records of cats with adrenal tumors secreting both aldosterone and progesterone were identified. Data concerning historical findings, clinicopathologic features, treatments, and outcomes were retrieved from medical records. Results: All 10 cats had diabetes mellitus in addition to biochemical features of hyperaldosteronism such as hypokalemia. High corticosterone concentrations were observed in all 3 cats in which this corticosteroid was measured. Ultrasound examinations revealed unilateral adrenal tumors in all 10 cases, and the contralateral adrenal gland was either atrophied or not identified in 5 cats. Three of 4 cats developed hypoadrenocorticism after surgical adrenalectomy. Three cats achieved diabetic remission after adrenalectomy. Two cats treated with adrenalectomy survived >1 year, 1 cat survived 6.5 months, and 1 cat was alive 5.5 months after diagnosis. Survival >1 year occurred in 2 of 4 cats treated with medical management alone. Two cats were not treated. Conclusions and Clinical Importance: The presence of multiple corticosteroid abnormalities should be considered in cats with aldosterone secreting adrenal tumors, especially those with concurrent diabetes mellitus. Both surgical and medical management can result in long‐term survival, although diabetic remission was documented only in cats undergoing adrenalectomy.